Android-Based Student Attendance Information System Using Real-Time Notification to Parents at Mts Wasilatul Huda Sukadana, East Lampung - Maulana Ihsan; Imam Mualim; Nuari Anisa Sivi (Al-Makki Publisher, 2026)
Student attendance recording at MTs Wasilatul Huda Sukadana, East Lampung, is currently managed manually using paper-based attendance books, resulting in delayed attendance recapitulation, the risk of document loss, and the absence of real-time communication with parents. Consequently, parents often remain unaware of their children's attendance status until the end of the semester, reducing opportunities for timely intervention. This study aims to develop an Android-based student attendance information system integrated with real-time parental notifications. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, including requirements analysis, UML-based system design, implementation using Flutter, Laravel RESTful API, MySQL, and Firebase Cloud Messaging (FCM), followed by Black Box Testing. The developed application enables teachers to record attendance through manual input or QR-code scanning, while parents instantly receive notifications containing attendance status, recording time, and remarks. Testing of 24 functional features achieved a 100% validity rate. Notification performance evaluation across 50 simulated attendance events showed a 100% delivery success rate with an average latency of 2.3 seconds. The average time for parents to receive attendance information decreased from several hours to less than five seconds. The study concludes that the system significantly enhances the timeliness, accuracy, and transparency of attendance communication between schools and parents, while supporting more effective monitoring of student attendance.